Structure-activity relationship of 7-aryl-2-anilino-pyrrolopyrimidines as Mer and Axl tyrosine kinase inhibitors - Shin Hyuck Chung; Jiwon Park; Jung Wuk Lee; Jiho Song; Danbee Jung; Kyung Hoon Min (Taylor & Francis Group, 2020)
The TAM (Axl, Mer, and Tyro3) family is implicated in the survival and chemoresistance of tumours and has emerged as a potential therapeutic target. A novel series of 7-aryl-2-anilino-pyrrolopyrimidines were identified as potent Axl/Mer tyrosine kinase inhibitors without significant inhibition of Tyro3. A representative compound 27 exhibited IC50 values of 2 nM and 16 nM for Mer and Axl, respectively, and considerable inhibition for Mer phosphorylation in cells. Docking studies suggested that the formation of a salt bridge between the nitrogen of the aniline moiety with ASP678 of the Mer kinase domain as well as an interaction with the hinge region that most kinase inhibitors have in common would be essential to retain activity. These results could provide useful information for finding promising inhibitors of Axl/Mer for the treatment of cancer.